Caminhos do horror: culpa e loucura em 1922 sob a influência de Poe - Freitas, Clarissa Paiva de (2021)
The general objective of this dissertation is to discuss the narrative choices made by author Stephen King in the short story 1922 and their relationship with the production of Edgar Allan Poe. We discussed King's choices and his narrative process from a comparative analysis with the short stories The Black Cat and The Tell Tale Heart, written by Poe – observing the traces of influence and innovations related to horror, terror and its surroundings to understand how a redesign of elements already known in the genre were fundamental to build “a horror” that approaches the classics in order to follow a tradition, however, innovating enough to reach the reader of the new era. For that, it started from the discussion of the genre and its variants and how their peculiarities give rise to multiple approaches, according to the scenario in which they were produced, and also by discussions guided by theorists who base the analysis, such as Tzvetan Todorov (2007), Louis Vax (1974), Ricado Pligia (1994), HP Lovecraft (1987), Remo Ceserani (2006), David Roas (2014), among others. Also analyzed “how”, “when” and “why” each significant element is inserted throughout the narratives and their impacts on the images that are formed in the reception of the text, contributing to the emotions of tension, horror and doubt to be installed on both sides (intra and extratextual). The journey sought, in particular, to understand the representation of horror from the veiled madness, the materialization of guilt and the ambiguous reactions that can result from this combination – both for the narrative and for the reader. To this end, a path was traced between Poe's tales and Stephen King's fiction – whose narratives reached prominence for exploring in a supernatural and psychological way the character blindness that inhabits man. In other words, this dissertation identified and discussed, through the comparison with Poe's two narratives, King's narrative choices, the text structure, the description of the characters – more emotional than physical –, as well as the growing psychic shock of the character, resulting in madness, as building and conducting elements of the plot culminating in the arc of horror. In the end, an overview of the writing, construction, growth and apex of horror was composed within 1922.